Caffeine content in energy drinks : deviation of declared from analytical value - Đureković, Monika (Array, 2019)
Convenient caffeine sources include energy drinks that are increasing in popularity among recreational and professional athletes, military personnel, young adults, and other consumers seeking ‘’energy boosters’’. Since energy drinks are a relatively concentrated source of caffeine, there is a risk of missing individually targeted caffeine intake or risk of inadvertently high intake with adverse effects. Therefore, the accuracy of declared caffeine content of energy drinks is highly important, especially from a consumer point. The purpose of this study was to determine caffeine content of 15 beverages available on the Croatian market and compare the analytical with the declared value. Caffeine was determined by high performance liquid chromatography technique with photodiode-array detection (HPLC-PDA). In 5 of total 15 products, a higher caffeine content was determined in average of 3.01 % than the one declared, resulting with increased intake of 4.75 mg caffeine/serving. In another 10 analysed products the content of caffeine was lower in average of 5.33 % (4.79 mg caffeine/serving) in compare to the one declared. Therefore, only with accurate information about the caffeine content in energy drinks may consumers and clinicians be assured of safe usage.